Advanced quasi-solid-state lithium-sulfur batteries: A high-performance flexible LiTa2PO8-based hybrid solid electrolyte membrane with enhanced safety and efficiency - Anbunathan, Ammaiyappan; Walle, Kumlachew Zelalem; Wu, She–Huang; Wu, Yi–Shiuan; Chang, Jeng-Kuei; Jose, Rajan; Yang, Chun-Chen (Elsevier Ltd, 2024)
Quasi-solid-state lithium-sulfur battery (QSSLSB) systems are more reliable and effective when considering safety and performance. This study employs a solution-casting method to create a self-supporting hybrid solid-state electrolyte (HSE) membrane. The membrane comprises a novel interconnected fast Li-ion conducting oxide, LiTa2PO8 (LTPO, filler); poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP, polymer matrix); lithium bis (trifluoromethanesulfonic) imide (LiTFSI, salt); and succinonitrile (SN, plasticizer). The as-prepared LTPOHSE composite membrane was assembled with a sulfurized polyacrylonitrile (SPAN) cathode and Li anode. The composite membrane exhibited good compatibility with the cathode, decreased the interfacial resistance, and delivered a higher Li+ ion transport number (ca. tLi + = 0.78). According to galvanostatic intermittent titration technique GITT test results, the 2032-type Li–S cells with LTPO-HSE membranes have an average Li+ ion diffusion coefficient of about 1.06 × 10− 10 cm2 s − 1 . Furthermore, the symmetrical cells that have Li metal and LTPO-HSE membrane exhibit smoother Li plating/stripping for 100 h at a current density of 1 mA cm− 2 . At 0.2C, the SPAN/LTPO-HSE/Li full cell exhibits a high initial capacity of 1189 mAh g− 1 , after 200 cycles, it maintained a specific capacity of 1118 mAh g− 1 with a steady Coulombic efficiency of 99.9 %. At a decay rate of 0.02 % per cycle, the capacity retention is 96 % (from the second cycle onward). Furthermore, our QSSLSB cell exhibits better capacity retention of 81 % after 350 cycles at 0.5C. In-situ microcalorimetry (MMC) revealed that the total exothermic heat generation (Qt) in coin cells based on quasi-solid LTPO-HSE membrane, cycling at 5C and 35 ◦C, was significantly lower (~60.2 % during discharge and 66.8 % during charge) that generated by the cells that use glass fiber separator with liquid-electrolyte GF-LE systems. Owing to its flexibility, better transference number, wider electrochemical window, and minimal heat generation, the as-prepared single-layer LTPO-HSE membrane is a promising solid-state electrolyte for future solid-state lithium-sulfur battery applications.